Risk factors predictors of the pattern of substance use during the adolescence. - Alfonso, José P.; Huedo-Medina, Tania B.; Espada, José P. (Anales de Psicología / Annals of Psychology, 2009)
The aim of this study was to estimate the relation between the pattern of alcohol, cannabis and tobacco use in adolescents and the so-cialization factors as predictors of consumption. The sample consisted of 292 students from 1st to 4th grade of secondary school. Several discrimi-nant models were defined as a function of different individual and sociali-zation variables. Firs, the high level of tobacco consume were distin-guished among those adolescents with a family education without well established norms, the existence of cannabis consume and an early age of onset. Secondly, the adolescents consumed more often when they had peers with favour attitudes to consume and they also used cannabis more often. Finally, the more consume of cannabis, the higher consume of tobacco and alcohol as well, easier access to drugs and more peers with positive attitudes and behaviours through the drugs. It is discussed the role of social, demographic and family variables as a risk factor for the transition from experimental to frequent use of substances in adolescence and the implications for the development of preventive programs.